2018
DOI: 10.1002/cam4.1842
|View full text |Cite
|
Sign up to set email alerts
|

Rs3212986 polymorphism, a possible biomarker to predict smoking‐related lung cancer, alters DNA repair capacity via regulating ERCC1 expression

Abstract: Single nucleotide polymorphisms (SNPs) in 3′UTR of key DNA repair enzyme genes are associated with inter‐individual differences of DNA repair capacity (DRC) and susceptibility to a variety of human malignancies such as lung cancer. In this study, seven candidate SNPs in 3′UTR of DRC‐related genes including ERCC1 (rs3212986, rs2336219, and rs735482), OGG1 (rs1052133), MLH3 (rs108621), CD3EAP (rs1007616), and PPP1R13L (rs6966) were analyzed in 300 lung cancer patients and controls from the northeast of China. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Our previous studies investigated genetic polymorphisms in the 3′‐untranslated region and a long noncoding RNA originating from ERCC1 and their use as biomarkers for prediction of repair of DNA damage and susceptibility to lung cancer. Our results indicate that ERCC1 is significantly regulated at the posttranscriptional level 7,16,17 . Alternative splicing is an important mechanism that regulates gene expression and generates RNA diversity 18 .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our previous studies investigated genetic polymorphisms in the 3′‐untranslated region and a long noncoding RNA originating from ERCC1 and their use as biomarkers for prediction of repair of DNA damage and susceptibility to lung cancer. Our results indicate that ERCC1 is significantly regulated at the posttranscriptional level 7,16,17 . Alternative splicing is an important mechanism that regulates gene expression and generates RNA diversity 18 .…”
Section: Introductionmentioning
confidence: 69%
“…However, when DNA repair by ERCC1 in damaged lung cells is insufficient, these cells cannot effectively remove the genetic damage caused by carcinogens, and this increases the risk of lung cancer 36 . Posttranscriptional regulation has a strong impact on the level of ERCC1 , and studies on lung cancer showed that noncoding RNA affect the susceptibility to environmental carcinogens and prognosis by regulating ERCC1 expression 7,16,17,37 . As a critical noncoding RNA produced by posttranscriptional regulation, circRNAs play important roles in tumors induced by carcinogens 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…CD3EAP (also known as ASE1, CAST, ERCC1 antisense) is a component of the RNA polymerase I complex, which is involved in ribosome biosynthesis and promotes cell proliferation similar to BYSL (54). CD3EAP has been reported to be involved in the occurrence and metastasis of lung cancer tissues (55).…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic studies had shown that rs3212986 and rs11615 ERCC1 gene polymorphisms may be a predictive factor for chemotherapy in NSCLC patients. Moreover, some polymorphic variants of these SNPs may affect the risk of lung cancer . Yu et al revealed that NSCLC patients carrying the A/A genotype in rs3212986 of ERCC1 gene had a higher risk of lung cancer, especially in the smoking population .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some polymorphic variants of these SNPs may affect the risk of lung cancer . Yu et al revealed that NSCLC patients carrying the A/A genotype in rs3212986 of ERCC1 gene had a higher risk of lung cancer, especially in the smoking population . Zhou et al observed that rs3212986 ERCC1 gene polymorphism may be a useful predictor of OS in advanced NSCLC patients treated with platinum‐based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%